Unveiling the professional attributes of university teachers - Dhunpath, Rubby; Biggs, Lynn; Dippenaar, Hanlie; Friedrich-Ne, Hesta; Joubert, Deidre; Nell, Ian; Yeats, Jacqueline (Critical Studies in Teaching and Learning, 2023)
This article derives from a collaborative higher education project, conceptualised, and implemented by academics from seven South African universities. These academics are members of the South African Teaching Advancement at University (TAU) Fellowship. The project has its roots in the Department of Higher Education’s National Framework for Enhancing Academics as University Teachers, which identifies six leverage points or ‘imperatives for action’, one of which is the imperative to develop expectations (attributes) of academics in their role as university teachers. TAU Fellows engaged in the collaborative enquiry over a period of three years, appropriating a conceptual framework posited by Henry Giroux, of teachers as transformative intellectuals. In this article, each author reflects on his/her own scholarship of teaching and learning (SoTL) endeavours, which provided the conceptual tools to illuminate what for them and the group, are valuable professional attributes. The metaphor of the Baobab tree is appropriated to signify ‘rhizomatic thinking’, which portrays teaching as subconscious, subversive, non-linear, multi-directional, serendipitous, esoteric, dynamic, unbounded, unpredictable, adaptive, and non-hierarchical. This SoTL enquiry enabled the TAU group to unveil and declare their professional attributes as they made public their praxis. The attributes include academics as imbued with the capacity for critical thinking and actively promoting critical thinking amongst their students; as active learning mediators; as responsive, innovative, and relevant curriculum designers; and as engaged professionals